Does the effect go up in smoke?: A randomized controlled trial of pictorial warnings on cigarette packaging - Schneider, Sven; Gadinger, Michael C.; Fischer, Andreas (Patient education and counseling, 2012)
Objective: Placing a combination of a written warning and a graphic image on cigarette packaging (so called “pictorial warnings”) is one of the WHO Framework Convention on Tobacco Control's most controversial recommendations. Our randomized controlled trial investigated if pictorial warnings lead to significantly higher motivation to quit, as compared to written warnings alone. Methods: Four pictorial warnings were selected from the EU Commission's official image catalogue. Study arm 1 (44 adult smokers) viewed only the written warnings while study arm 2 (44 adult smokers) viewed the corresponding pictorial warnings. Self-affirmation was a second randomly manipulated factor, and nicotine dependence a quasi-experimental third factor. The main outcome measured was the motivation to quit, with fear intensity as one of the secondary outcomes. Results: Pictorial warnings were associated with a significantly higher motivation to quit. A pictorial warning was also associated with higher fear intensity. The effect of warnings appears to be independent of nicotine dependence and self-affirmation. Conclusions: Nationwide implementation of pictorial warnings may be effective in increasing heavy smokers’ motivation to quit. Practice implication: Due to the fact that perceived vulnerability, response and self-efficacy are not more strongly affected by pictorial warnings this effect may turn out to be short-term.
Available online 8 April 2011
Gesehen am 02.07.2018